LEVERAGING FINTECH INNOVATIONS TO ENHANCE FINANCIAL MANAGEMENT EFFICIENCY: A COMPREHENSIVE ANALYSIS OF IMPLEMENTATION STRATEGIES AND IMPACT ON ORGANIZATIONAL PERFORMANCE - Hermiyetti Hermiyetti (CV. Adiba Aisha Amira, 2025)
This research delved into the transformative potential of leveraging FinTech innovations to enhance financial management efficiency, offering a comprehensive analysis of implementation strategies and their impact on organizational performance. Employing a retrospective lens, the study investigated the historical evolution of FinTech, tracing its trajectory from rudimentary online banking to the sophisticated ecosystem encompassing artificial intelligence, blockchain, and data analytics. The research scrutinized various FinTech applications, including automated financial planning tools, digital payment systems, robo-advisors, and blockchain technology, highlighting their role in optimizing financial processes. Implementation strategies were systematically examined, considering user acceptance, regulatory compliance, and technological integration. The study adopted a rigorous approach to evaluate the impact of FinTech adoption on organizational performance, emphasizing improvements in speed, accuracy, decision-making, and cost efficiencies. Through a synthesis of successful case studies and empirical research, the research identified vital findings, informing both practitioners and policymakers. This comprehensive analysis contributes valuable insights to the ongoing discourse on FinTech, offering practical guidance for organizations seeking to harness its potential for building a more efficient and resilient financial ecosystem.